Easy-to-Use Cloud Computing for Teaching Data Science. (1st January 2021) - Kim, Brian; Henke, Graham
ABSTRACT: One of the biggest hurdles of teaching data science and programming techniques to beginners is simply getting started with the technology. With multiple versions of the same coding language available (e.g., Python 2 and Python 3), various additional libraries and packages to install, as well as integrated development environments to navigate, the first step can be the most daunting. We show the advantages of using cloud computing to solve this issue and demonstrate one way of implementing it to allow beginners to get started with coding immediately. Using user-friendly Jupyter notebooks along with the interactive capabilities possible through Binder, we provide introductory Python and SQL material that students can access without downloading anything. This lets students to get started with coding right away without getting frustrated figuring out what to install. Example introductory modules on using Python and SQL for data analysis are provided through GitHub at https://github.com/Coleridge-Initiative/ada-intro-python and https://github.com/Coleridge-Initiative/ada-intro-sql .